PENGARUH JOB EMBEDDEDNESS, KEPUASAN KERJA, DAN KOMITMEN ORGANISASIONAL TERHADAP TURNOVER INTENTION KARYAWAN - Putri Rarasanti, Ida Ayu; Suana, I Wayan (E-Jurnal Manajemen; Vol 5 No 7 (2016), 2016)
This study was conducted to determine the effect of job embeddedness, job satisfaction, and organizational commitment on employee turnover intention on PT. Karya Luhur Permai. The study was conducted on employees PT. Karya Luhur Permai by the number of respondents as many as 147 employees. The number of respondents is determined proportional stratified random sampling technique. The data collection is done by distributing questionnaires using a 5-point Likert scale to measure 17 indicators. Data analysis technique used is multiple linear regression. The test results job embeddedness negative and significant impact on employee turnover intention, job satisfaction negative and significant impact on employee turnover intention, as well as organizational commitment negative and significant impact on employee turnover intention. The limitation of this study is the location of this research will be in the scope of the PT. Karya Luhur Permai. so the results of this study can not explain the circumstances of the other PT. besides PT. Karya Luhur Permai.
Keywords: job embeddedness, job satisfaction, organizational commitment, turnover intention